Partie orientale de la Nouvelle France ou du Canada - Bellin, Jacques Nicolas, 1703-1772 ([Nürnberg?], 1755)
Colour. Decorative title cartouche. Relief shown pictorially. Depths shown by soundings. Two bar scales: common French leagues, and French and English common marine leagues. CNS maps no. 380.